Pengembangan Model Bahan Ajar Berbasis Canva untuk Materi Tematik pada Kelas 2 di SDN Tangerang 15 - Magdalena, Ina; Anggraeni, Ani Nur; Wahyu, Rahma Rizkiya (ANWARUL, 2023)
In the world of education, it is necessary to focus on teaching material models to be applied or implemented to students in the learning process so that they can be effectively adapted to achieve the goal, namely student learning outcomes. So that by utilizing the appropriate model of teaching materials it will be effective in increasing the motivation and also the learning outcomes of students at school. Particular attention is paid to the use of online media or the CANVA platform used by Tangerang 15 Elementary School to be precise for Grade 2 students to be one of the efforts of a teacher to increase motivation and also interest students in the learning process. The method used in this research is literature study by utilizing several journals as well as previous literacy related to the topic taken by the researcher. From the results of research that has been carried out by utilizing several previous studies also that by utilizing learning media on the CANVA platform it is very suitable to be applied in order to increase motivation and also learning outcomes for class 2 students at SDN Tangerang 15 because it utilizes audio-visual, color features, audio, characters, illustrations, photos, and others that can be adapted to the creativity of students and can enhance their ideas and creativity, especially in thematic subjects.